Enumerating bone marrow blasts from nonerythroid cellularity improves outcome prediction in myelodysplastic syndromes and permits a better definition of the intermediate risk category of the Revised International Prognostic Scoring System (IPSS‐R). Issue 7 (9th May 2017) - Calvo, Xavier; Arenillas, Leonor; Luño, Elisa; Senent, Leonor; Arnan, Montserrat; Ramos, Fernando; Pedro, Carme; Tormo, Mar; Montoro, Julia; Díez‐Campelo, María; Blanco, María Laura; Arrizabalaga, Beatriz; et al.
Abstract: The Revised International Prognostic Scoring System (IPSS‐R) has been recognized as the score with the best outcome prediction capability in MDS, but this brought new concerns about the accurate prognostication of patients classified into the intermediate risk category. The correct enumeration of blasts is essential in prognostication of MDS. Recent data evidenced that considering blasts from nonerythroid cellularity (NECs) improves outcome prediction in the context of IPSS and WHO classification. We assessed the percentage of blasts from total nucleated cells (TNCs) and NECs in 3924 MDS patients from the GESMD, 498 of whom were MDS with erythroid predominance (MDS‐E). We assessed if calculating IPSS‐R by enumerating blasts from NECs improves prognostication of MDS. Twenty‐four percent of patients classified into the intermediate category were reclassified into higher‐risk categories and showed shorter overall survival (OS) and time to AML evolution than those who remained into the intermediate one. Likewise, a better distribution of patients was observed, since lower‐risk patients showed longer survivals than previously whereas higher‐risk ones maintained the outcome expected in this poor prognostic group (median OS < 20 months). Furthermore, our approach was particularly useful for detecting patients at risk of dying with AML. Regarding MDS‐E, 51% patients classified into the intermediate category were reclassified into higher‐risk ones and showed shorter OS and time to AML. In this subgroup of MDS, IPSS‐R was capable of splitting our series in five groups with significant differences in OS only when blasts were assessed from NECs. In conclusion, our easy‐applicable approach improves prognostic assessment of MDS patients.